Cholera toxin B scaffolded, focused SIV V2 epitope elicits antibodies that influence the risk of SIVmac251 acquisition in macaques - Rahman, Mohammad Arif; Becerra-Flores, Manuel; Patskovsky, Yury; Silva de Castro, Isabela; Bissa, Massimiliano; Basu, Shraddha; Shen, Xiaoying; Williams, LaTonya D.; Sarkis, Sarkis; N’guessan, Kombo F.; LaBranche, Celia; Tomaras, Georgia D.; et al. (Frontiers in Immunology, 2023)
An efficacious HIV vaccine will need to elicit a complex package of innate, humoral, and cellular immune responses. This complex package of responses to vaccine candidates has been studied and yielded important results, yet it has been a recurring challenge to determine the magnitude and protective effect of specific in vivo immune responses in isolation. We therefore designed a single, viral-spike-apical, epitope-focused V2 loop immunogen to reveal individual vaccine-elicited immune factors that contribute to protection against HIV/SIV. We generated a novel vaccine by incorporating the V2 loop B-cell epitope in the cholera toxin B (CTB) scaffold and compared two new immunization regimens to a historically protective ‘standard’ vaccine regimen (SVR) consisting of 2xDNA prime boosted with 2xALVAC-SIV and 1xΔV1gp120. We immunized a cohort of macaques with 5xCTB-V2c vaccine+alum intramuscularly simultaneously with topical intrarectal vaccination of CTB-V2c vaccine without alum (5xCTB-V2/alum). In a second group, we tested a modified version of the SVR consisting of 2xDNA prime and boosted with 1xALVAC-SIV and 2xALVAC-SIV+CTB-V2/alum, (DA/CTB-V2c/alum). Strikingly, V2c was highly immunogenic when incorporated in the CTB scaffold. In the absence of any other anti-viral antibodies, the anti-V2c antibodies induced by vaccination were highly functional. 5xCTB-V2c/alum vaccination mediated non-neutralizing ADCC activity and efferocytosis, but produced low avidity, trogocytosis, and no neutralization of tier 1 virus. Furthermore, DA/CTB-V2c/alum vaccination also generated lower total ADCC activity, avidity, and neutralization compared to the SVR. These data suggest that the ΔV1gp120 boost in the SVR yielded more favorable immune responses than its CTB-V2c counterpart. Vaccination with the SVR generates CCR5- α4β7+CD4+ Th1, Th2, and Th17 cells, which are less likely to be infected by SIV/HIV and likely contributed to the protection afforded in this regimen. The 5xCTB-V2c/alum regimen likewise elicited higher circulating CCR5- α4β7+ CD4+ T cells and mucosal α4β7+ CD4+ T cells compared to the DA/CTB-V2c/alum regimen, where the first cell type was associated with reduced risk of viral acquisition. Taken together, these data suggest that individual viral spike B-cell epitopes can be highly immunogenic and functional as isolated immunogens, although they might not be sufficient on their own to provide full protection against HIV/SIV infection.